Vegetated Steel Slag Substrate Constructed Wetlands can Achieve High Efficiency Simultaneous Nitrogen and Phosphorus Removal - Zhang, Jingyao; Zou, Yuanchun; Yu, Xiaofei; Ding, Shanshan; Yan, Jiawen; Min, Yongen (Frontiers in Environmental Science, 2022)
Steel slag substrate constructed wetlands (SSCWs) can effectively remove phosphorus (P) from sewage through Ca-P precipitation and adsorption. Yet, the disadvantages of a high pH value of the effluent and low nitrogen (N) removal efficiency limit the practical application of SSCWs. To improve these shortcomings, plant cultivation and combining steel slag with other substrate materials have been applied in SSCWs. However, related studies have not obtained a unanimous consensus elucidating such improvements. To accurately evaluate improvement, we statistically analyzed the experimental data reported in 27 related papers and found that combining steel slag with other substrate materials in SSCWs significantly increased the removal amount of total nitrogen (TN) (51.58 mg TN/L) and ammonium nitrogen (NH4+-N) (74.15 mg NH4+-N/L) but reduced the removal amount of total phosphorus (TP) (7.76 mg TP/L). Plant cultivation in these combined substrate SSCWs could compensate for the decline in TP removal amount and improve upon the simultaneous removal of N and P (6.02 mg TP/L, 62.18 mg TN/L, and 69.16 mg NH4+-N/L). Moreover, compared with vertical flow SSCWs, horizontal flow enables plant-cultivated and combined substrate SSCWs to achieve a higher TP removal capacity (6.38 mg TP/L). In addition, operational parameters, including temperature, hydraulic retention time (HRT), pH value and influent concentration, significantly affected the N and P removal capacity of SSCWs. Our research results provide a theoretical reference for the design and operation of SSCWs for efficient N and P removal.